Testicular ultrastructure and morphology of the seminal pathway in Prochilodus scrofa - Vicentini, Carlos Alberto [UNESP]; Franceschini-Vicentini, I. B. [UNESP]; Benetti, E. J. [UNESP]; Orsi, A. M. [UNESP] (My University, 2001)
The seminiferous tubules of Prochilodus scrofa present a coiled morphological arrangement with intertubular anastomoses and unrestricted spermatogonial distribution. The structural pattern of the seminiferous tubules is cystic, with cysts formed by cytoplasmic prolongations of Sertoli cells. Inside the cysts are observed different types of germ cells. The seminiferous tubules open individually on the ventral surface of the main testicular duct present in each testis. Each main testicular duct prolongs as a spermatic duct, fusing with the spermatic duct of the opposite side to form the common spermatic duct which opens into the urogenital papilla. The mature sperm cysts break and extravasate their content into the lumen of the seminiferous tubules from which the seminal fluid and the spermatozoa penetrate the main testicular duct, the spermatic duct and the common spermatic duct for semen ejaculation.
Keywords: Seminal pathway; Teleost fish; Testis; Ultrastructure; animal; fish; histology; male; physiology; seminiferous tubule; spermatogenesis; spermatogonium; ultrastructure; Animals; Corrosion Casting; Fishes; Male; Seminiferous Tubules; Spermatogenesis; Spermatogonia